New data on the wolf spiders of Iran (Arachnida: Aranei: Lycosidae), with a description of two new species - Shafaie Sepideh; Koponen Seppo; Nadolny Anton A; Kunt Kadir Bogac; Mirshamsi Omid (KMK SCIENTIFIC PRESS LTD, MOSCOW STATE UNIV, 2022)
New taxonomic and faunistic data on 25 species in 13 genera of Lycosidae from Iran are provided. Two new species Alopecosa pekari sp.n. (male) and Trochosa marusiki sp.n. (male) are diagnosed and described from West Azerbaijan Province. The genus Draposa Kronestedt, 2010 and the species Draposa oakleyi (Gravely, 1924), Evippa eltonica Dunin, 1994, Karakumosa turanica Logunov et Ponomarev, 2020 and K. zyuzint Logunov et Ponomarev, 2020 are recorded from Iran for the first time. Thirteen new provincial records are also provided. The known lycosid fauna of Iran contains now 81 species.